Nylon Calculus: Offseason movement and offensive styles - Levy, I. (2017)
Right through the end of August, the NBA offseason has been loaded with the movement of All-Stars and top-tier talents. Questions of team fit are all hypothetical until full rosters are actually set and teams take the floor, but I thought it might be fun to look at some of the biggest moves through the lens of offensive style charts - highlighting places where players may need to adapt to their new teams and vice versa.